Dental Malpractice in Implant Dentistry in Saudi Arabia - Al-Safadi, Rahaf; Al-Safadi, Riham; Al-Safadi, Reef; Al-Jahdali, Sultan; Al-Hamidi, Abdulrahman; Al-Khuraisi, Bandar; Al-Malki, Talal; Al-Gannass, Thamer; Al-Arjani, Mutaz; Al-Alawi, Hasan (International Journal of Emerging Trends in Science and Technology, 2019)
Aim: The aim of this study was to detect and analyze dental malpractice in the field of implant dentistry in the Kingdom of Saudi Arabia. Materials and Methods: 106 patients aged ≥ 18 years with at least one professional malpractice in implant dentistry done in dental health premises in Saudi Arabia were included in the study. Clinical and radiographic examinations were used to detect preoperative (diagnosis and treatment planning), intraoperative (implant insertion), and postoperative (post surgery and prosthesis) complications. The data obtained including age and gender were documented in a patient examination form then statistically analyzed using Chi-Square Test and Spearman’s Correlation Coefficient. Results: The percentages of patients were equally divided among the preoperative, intraoperative, and postoperative phases p > 0.05. More than half of the patients were females (61.3%). The majority of the patients were in the age group 50-60 years. Also, the majority of the patients had implants with malpractice placed in the posterior region. Exactly half of the patients had implants with malpractice placed in the maxilla. In addition, exactly half of the patients had technical errors violating the surrounding structures; (37.7%) of the patients had damage to adjacent tooth and (11.3%) had inferior alveolar nerve damage; also, (4.7%) of them had sinus penetration. Furthermore, at the patient level, age and gender were not related to implant failure, and (75.5%) of the patients had implant failure. With respect to peri-implantitis, patients ≥ 50 years of age were more than patients < 50 years of age. However, gender and maxilla were not related to peri-implantitis. The prevalence of peri-implantitis was 20.8% at the patient level. In partially edentulous patients, implant fracture was (1.17%) at the implant level. Conclusion: Implant malpractice equally occurred among the preoperative, intraoperative, and postoperative phases. Keywords: Failure, Implant, Intraoperative, Malpractice, Peri-implantitis, Postoperative, Preoperative.